ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA DALAM MEMBUAT MIND MAPPING PADA MATERI SISTEM EKSKRESI PADA MANUSIA - Leny Vivi Palufi; An Nuril Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aims to determine the effect of problems with mind maps in measuring students' conceptual understanding and student learning outcomes in making mind maps on the human excretory system for grade VIII junior high school students. The data collection method used is to collect data in the form of quasi-experiments which only require one class without a control class. The design of this research is the One-Shot Case Study. The data analysis technique used in this method is descriptive qualitative. The assessment instrument obtained in this study was in the form of data on students' understanding abilities in making mind maps, questionnaires and interviews. The data obtained will be carried out based on rubric analysis related to students' understanding of concepts through the creation of a mind map project. The research subjects were students of class VIII-E at SMP Negeri 2 Bojonegoro which opened 32 students. The results showed that the use of learning outcomes in the form of mind maps helped students understand the concept of learning in the human excretory material system. As for the results of the study, it can be seen that student learning outcomes in understanding concepts to produce mind map products are in good category. The overall ability of students in making mind maps is 25% very good, 67% in good category and 8% with categories. In addition, 53.3% of students responded well, applied learning to produce mind map products.